Aplicação catalítica de peneiras moleculares básicas micro e mesoporosas Catalytic applications of basic micro and mesoporous molecular sieves - Leandro Martins; Dilson Cardoso (Química Nova, 2006)
Catalysis by solid acids has received much attention due to its importance in petroleum refining and petrochemical processes. Relatively few studies have focused on catalysis by bases and even les on using basic molecular sieves. This paper deals with the potential application of micro and mesoporous molecular sieves in base catalysis reactions. The paper is divided in two parts, the first one dedicated to the design of the catalysts and the second to some relevant examples of catalytic reactions, which find a huge field of applications essentially in the synthesis of fine chemicals. Here, recent developments in catalysis by basic molecular sieves and the perspectives of applications in correlated catalytic processes are described.